2014
DOI: 10.1049/iet-syb.2013.0012
|View full text |Cite
|
Sign up to set email alerts
|

On the design of human immunodeficiency virus treatment based on a non‐linear time‐delay model

Abstract: Mathematical modelling and methods from control theory can be employed to find appropriate drug regimens in human immunodeficiency virus (HIV) treatment. In this study, using a non-linear time-delay model, the authors design some suboptimal highly active antiretroviral therapy (HAART) [http://www.en.wikipedia.org/wiki/Protease_inhibitor_%28pharmacology%29] regimens for patients with HIV. The non-linear delayed model is used to describe the dynamical interactions between HIV and human immune system in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Moreover, in [30], The state‐dependent Riccati equation based on pseudo‐linearisation factorisation is proposed to control autonomous underwater vehicles. The pseudo‐linearisation technique is extended for non‐linear time‐delay systems [3133]. In [31], suboptimal sliding mode controller is designed for non‐linear time‐delay systems based on extended pseudo‐linearisation.…”
Section: Extended Pseudo‐linearisation Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in [30], The state‐dependent Riccati equation based on pseudo‐linearisation factorisation is proposed to control autonomous underwater vehicles. The pseudo‐linearisation technique is extended for non‐linear time‐delay systems [3133]. In [31], suboptimal sliding mode controller is designed for non‐linear time‐delay systems based on extended pseudo‐linearisation.…”
Section: Extended Pseudo‐linearisation Techniquementioning
confidence: 99%
“…In [31], suboptimal sliding mode controller is designed for non‐linear time‐delay systems based on extended pseudo‐linearisation. Also, based on this approach, suboptimal observer [32] and controller [33] are presented for non‐linear time‐delay systems. Applying the extended pseudo‐linearisation approach, the presented observer can be utilised for several kinds of non‐linear time‐delay systems such as systems with multiple discrete delays, time‐varying delay and distributed delay.…”
Section: Extended Pseudo‐linearisation Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this algorithm is useless under the rapid variation of environmental conditions. [13][14][15] Several papers have suggested a combination of the RCC [16][17][18][19] and MRAC 20,21 to better the underdamped response of PV systems after fast changes of the duty cycle. 7,8 It is shown that the INC technique works well in fast varying environmental conditions, but the main drawback is that this algorithm needs complex hardware and software resulting increase of cost.…”
Section: Introductionmentioning
confidence: 99%
“…9 Therefore, the ideal MPPT algorithm is straightforward and low-cost and reaches the MPP with least oscillations. [13][14][15] Several papers have suggested a combination of the RCC [16][17][18][19] and MRAC 20,21 to better the underdamped response of PV systems after fast changes of the duty cycle. The RCC unit accepts the array voltage and power as inputs and generates the duty cycle.…”
Section: Introductionmentioning
confidence: 99%